Hard currency and financial development - Ilan Goldfajn; Roberto Rigobon (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2000)
This paper investigates the relationship between hard currency and financial development. It creates four different series of hard currency based on different sets of data. The results of the paper suggest that indeed financial development and the hardness of currencies are highly correlated. However, we find that the relationship from currency hardness to financial development is fully captured by macro variables that represent overall macroeconomic stability. This suggest that having a hard currency is not a pre-condition for financial development but rather establishing a macroeconomic stable environment.
Keywords: 330